Sport parenting during the COVID-19 pandemic: Perceptions of parents and youth in Australia. (January 2023) - Elliott, Sam; Pankowiak, Aurélie; Eime, Rochelle; Drummond, Murray
Abstract: Understanding the impact of the COVID-19 pandemic on parental involvement in youth sport is largely unknown. The objective of the study presented in this paper was to understand parental involvement in relation to their child's participation in organised sport during the COVID-19 pandemic. Using an interpretive descriptive methodology, online qualitative interviews and online focus groups with parents and youth (15–18 years) (n = 29) were conducted during June 2020. Following a rigorous reflexive thematic analysis, four themes illustrated the nature of sport parenting during this stressful and uncertain period: (a) reshaping sport parenting identity, (b) the unexpected growth of sport parenting responsibilities, (c) responding to children's loss of sport, and (d) policies impact family commitment and attitudes to returning to sport. The findings are discussed considering Harwood and Knight's (2015) postulates of parenting expertise in sport and offer potential ideas to better support parents and children situated in unexpectedly stressful situations. Highlights: Parents reshaped their sport identity during the first wave of the COVID-19 pandemic. Parents experienced a rapid and unexpected growth in responsibility as a sport parent. Parental attunement and responsiveness to their children's needs was higher during lockdown. Constant policy changes challenged parents' capacity to provide logistical support.